Civil Commitment - Heilbrun, Kirk; DeMatteo, David; Holliday, Stephanie Brooks; LaDuke, Casey (Forensic Mental Health Assessment, 2014)
This chapter focuses on the impact of forensic assessment on civil commitment decisions. Civil commitment questions can, in some cases, involve committed individuals exercising legitimate legal rights to secure their release, sometimes against medical advice. Therefore, the results of a FMHA in this context can be subject to adversarial scrutiny in the same way as could other kinds of FMHA. Civil commitment as a form of FMHA has received less attention than other evaluations conducted in the course of different kinds of civil and criminal litigation. This has changed some in recent years, as reflected by the excellent summary of this issue from both a clinical and legal perspective that highlights implications for evaluation